2019
DOI: 10.3390/sci1030062
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Evaluation of an UWB Localization System for Industrial Applications

Abstract: Many applications in the context of Industry 4.0 require precise localization. However, indoor localization remains an open problem, especially in complex environments such as industrial environments. In recent years, we have seen the emergence of Ultra WideBand (UWB) localization systems. The aim of this article is to evaluate the performance of a UWB system to estimate the position of a person moving in an indoor environment. To do so, we implemented an experimental protocol to evaluate the accuracy of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…(1) Kalman filter (KF). Kalman [10] proposed a new method for linear filtering and prediction problems, which used the linear system state equation to observe system input and output data in order to best estimate the state of the system. Benefiting from the advantages of strong real-time performance, high speed, and high efficiency, the KF has been widely used in anti-interference [11].…”
Section: Related Workmentioning
confidence: 99%
“…(1) Kalman filter (KF). Kalman [10] proposed a new method for linear filtering and prediction problems, which used the linear system state equation to observe system input and output data in order to best estimate the state of the system. Benefiting from the advantages of strong real-time performance, high speed, and high efficiency, the KF has been widely used in anti-interference [11].…”
Section: Related Workmentioning
confidence: 99%
“…The global navigation satellite system (GNSS) is the dominating technology for global positioning systems (GPSs), but since the GNSS signals are not able to penetrate buildings, other technologies should be used for indoor positioning systems (IPS). Methods using WiFi, ultra-wideband (UWB) [ 10 ], Zigbee [ 11 ], or visible light communication (VLC) were proposed. WiFi is often used for coarse urban localization with accuracy of tens of meters, but some methods for IPS were also developed [ 12 ].…”
Section: Iot/ble-based Positioning and Tracking Systemsmentioning
confidence: 99%
“…However, this architecture presents a major disadvantage from our point of view: each tag to be located can only measure ranges with a maximum of four anchors. The same Decawave system that is going to be explored in this paper (MDEK1001) was recently studied by Delamare [ 21 ] and found that using only four ranges was limiting, and they concluded that a larger number of anchors should be used for better accuracy.…”
Section: Introductionmentioning
confidence: 99%